SURVEY MINAT MAHASISWA UNTUK MENGIKUTI UJIAN SERTIFIKASI AKUNTAN PUBLIK (USAP) - Mas'ud Machfoedz (Journal of Indonesian Economy and Business (JIEB), 1998)
The government of Indonesia through Minister of Finance Decree No 43/KMK. 017/ 1997 slated that all accountants whose intend to run accountant public offices should take Certified Public Accountant Exam (USAP). The exam will be conducted and operated by special committee that will be appointed by Indonesian Institute of Accountants (1AI). This exam may be taken by anyone holding SI degree in accounting (equivalent undergraduate degree). Accounting graduate holding degrees may choose to take this exam when he/she want to open a public accounting office in the future. The 'animo' and motivation of accountant candidates are still questionable whether they are interested to take or not to take this exam after they will hold degree in accounting.This study intents to answer the question: what are the factors that influence the intention of accounting degree candidates to take USAP. The respondents are thefinal semester students of accounting department economic faculties and collegesaround Yogyakarta. 440 students participated in this survey covering seven universities and colleges. The results indicate that the factor of quality is the mostimportant factor in taking the USAP, followed by career and economic factors. Theother results show that genders, income, and family factors do not influence theintention to take the exam. Intuitively, it can be concluded that those students beingstudied fee! that the improving quality by taking USAP is important to improve professionalism facing the keener competition in 21" century.